Nalar Maslahat Dalam Kebijakan Zonasi Dan Penguatan Pendidikan Karakter - Firman Muhammad Arif (IQRO: Journal of Islamic Education, 2019)
Zoning Policy and Character Education Strengthening  are government policies in the education sector. Zoning policy aims at efforts to restore national education and strengthen character   education   aimed   at   developing   religious   values   which   then   accelerate   the strengthening of individual character so that they are able to control themselves and develop noble character in society and nationhood. Mass  reasoning  contained  in  the  qawa'id fiqhiyyah and  usul al-fiqh is  used  as  an instrument  to  measure the  weight  of maslahat  contained in government  education  policies. Zoning policies and strengthening character education are considered as media to achieve goals. The mass content  contained  in the  zoning policy shows maximum weight  than  the mafsadah (something bad or potentially bad). National education arrangement that prioritizes citizenship character has triggered the government to issue a policy to strengthen  character education with the maslahat (something good, potentially good) weight with consideration of the sociological, cultural and political aspects of the local government. The manifestation  of strengthening character education is full day school allowing it to be applied in urban school areas and vice versa will increase the heavy burden of parents and students in various schools in rural areas so that full day school is not forced but chosen.